An Orientalist Reading of Swarup ’s “Q & A” 2005 and Boyle’s “Slumdog Millionaire ” 2008 within a Post - Colonial Frame - Zergat,Mounir; Aroussi,Mohamed; Selt, Djihad Afaf (University of Ammar Theledji -Laghouat, 2021)
This work as a dissertation examines Orientalism in Vikas Swarup novel “Q & A” and its cinematic adaptation, the movie of Danny Boyle entitled “Slumdog Millionaire”. Historically speaking, Edward Said in his significant book entitled Orientalism brought upon the world a new and deep meaning of both culture and society by taking his audience back in time from which these perspectives originate in the first place. He explains in his work that Orientalism in not just the academic field presented to people but rather a false man-made representation of the Orient which is considered as a strong and dangerous weapon of political oppression and dominance over which that Orient has no objection. The strong colonizer imposed a language and culture, while the Oriental peoples' languages and cultures were neglected or twisted. Thus, this work further aspires to show Orientalism within the Post-Colonial work “Q & A” and its adaptation as a movie “Slumdog Millionaire”. Saidian Orientalism and Postcolonialialism were influential theories in the creation of Third World Literature, also known as protest literature or counter discourse literature. Using the latter, we have used a descriptive method along with an analytical one to prove that the Indian diplomat, Vikas Swarup wrote a marvellous novel called “Q & A” to show the harsh and abusive influence of the Westerners on his country through a story of Ram Mohammad Thomas, a teenage waiter who rises from poverty and slum to become the world's most famous quiz show winner, yet only to be caught and imprisoned on charges of cheating at the end. Finally, the research concludes with the critical truth that Swarup, in his book, showed his audience that it was the colonizer who made the Indians as scattered, weak, poor and dirty as they appear to the world. As a reply to him then, the worldwide-famous movie “Slumdog Millionaire” was made to receive a big hit globally to the extent of making Swarup‟s novel even more famous. Danny Boyle, a British film maker, took the initiative of making a movie out of the novel as Westerners claimed. But, in fact, Boyle and his crew took advantage of the situation and created what their people and ancestors used to depict, a false image, a brutal, exotic, and horrible image of the Orient in the shoes of the Indian community this time